Approaches and Models for Application of Gamification Techniques in v-Learning - Tramonti, Michela; Dochshanov, Alden; Monova-Zheleva, Mariya; Zhelev, Yanislav (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2021)
Nowadays, the effectiveness of technology integration into teaching and learning approaches is widely recognised, mainly, in those pedagogical practices where students are the centre and co-constructors of their knowledge process. Specifically, the authors underline the potentialities of combining the gamification techniques and 3D virtual environments to design innovative learning settings through the description of two projects, TALETE and AVATAR, funded by the European Commission.
Keywords: Gamification Concept; Virtual Reality; v-Learning; e-Tivities Model